Mother's Curse - Okoye, Hero (Nigeria, 2012)
Emma pledged to himself not to look, but at one side of life, the permitted side, not as a man but as a Christian. He has bound his eyes with another's handkerchief. His mother was deeply in love with him, but when the intervals of darkness come, as come they must, when the sun is hidden and the stars stop shinning the same mother placed a curse on him...
Keywords: Juvenile Fiction